TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PROSES PEMBELAJARAN - Wawan Suharmawan & Is Eka Herawati (IAIN PAREPARE, 2015)
Basically learners have the imagination and curiosity. Both are authorized for developing attitudes and critical and creative thinking can not be separated from the information and communications conveyed. Therefore, learning activities need to be made if the land in order to become a fertile place for the development of both the potential of God's grace. Learning atmosphere accompanied by praise of teachers towards the students 'work, which is accompanied by a teacher's question that challenge and encouragement so that students conduct experiments is a good learning to develop students' potential. Information and communication technology can be a means to facilitate learning that can be digested and received with both an appropriate means of beginning the learning success.